2006
DOI: 10.1021/bi0600300
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of 40 Human Melanocortin-4 Receptor Polymorphisms with the Endogenous Proopiomelanocortin-Derived Agonists and the Agouti-Related Protein (AGRP) Antagonist,

Abstract: The melanocortin-4 receptor (MC4R) is a G-protein coupled receptor (GPCR) that is expressed in the central nervous system and has a role in regulating energy homeostasis and obesity. Up to a remarkable 6% of morbidly obese adults and children studied possess single nucleotide polymorphisms (SNPs) of the MC4R. Upon stimulation by agonist, the MC4R signals through the intracellular adenylate cyclase signal transduction pathway. Posttranslational modification of the pro-opiomelanocortin (POMC) gene transcript res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
160
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(183 citation statements)
references
References 72 publications
16
160
3
4
Order By: Relevance
“…About 6% of severe obese subjects carry point mutations in or near the MC4R gene [15,38,50]. Investigation of signaling activities of these mutant MC4Rs in assays based on cell culture demonstrated that the characteristic of obesity correlates with dysfunctions in receptor properties [14,25,39,52]. The most common MC4R polymorphism V103I is negatively associated with obesity [18], a finding meanwhile replicated in several independent studies [18,23,47,53].…”
Section: Mouse Models For the Analysis Of Gene Variantsmentioning
confidence: 90%
See 1 more Smart Citation
“…About 6% of severe obese subjects carry point mutations in or near the MC4R gene [15,38,50]. Investigation of signaling activities of these mutant MC4Rs in assays based on cell culture demonstrated that the characteristic of obesity correlates with dysfunctions in receptor properties [14,25,39,52]. The most common MC4R polymorphism V103I is negatively associated with obesity [18], a finding meanwhile replicated in several independent studies [18,23,47,53].…”
Section: Mouse Models For the Analysis Of Gene Variantsmentioning
confidence: 90%
“…Despite of a negative association of V103I with obesity, a strong pharmacological phenotype of this mutant receptor expressed in cell culture was not identified. Only one report demonstrated a lower potency of orexigenic AGRP on V103I corresponding to the distribution of this allele in population screens [52]. Several point mutations in the Mc4r gene introduced by chemical mutagenesis have been shown to cause different severity of obesity in mice [40].…”
Section: Mouse Models For the Analysis Of Gene Variantsmentioning
confidence: 99%
“…Only one of the 11 non-synonymous mutations (N62S) exhibited a reduced function, as indicated by a strongly reduced cell surface expression, and by signal transduction Table 2 MC4R functional assays MC4R cAMP accumulation and cell surface expression assays. Each amino acid replacement observed in the HGDP-CEPH panel is found in Table. Three sites (R7C, V103I, I251L) were not functionally tested in this study as these sites have been identiWed and assayed previously (Srinivasan et al 2004;Stutzmann et al 2007;Xiang et al 2006). Construct properties that did not result in an enhancement of intracellular cAMP levels (Table 2).…”
Section: Functional Characterization Of Non-synonymous Mutationsmentioning
confidence: 99%
“…INSIG2 rs7566605 and MC4R rs2229616 were the first SNPs with a replicated polygenic effect on body mass in the general population 3,4 and known functional implications. 5,6 The INSIG2 region has been connected with obesity in human linkage studies 7 as well as in one of the first genome-wide association studies (GWAS) 3 to address obesity. This GWAS identified common variant rs7566605, located 10-kb upstream of the INSIG2 transcription start site.…”
Section: Introductionmentioning
confidence: 99%
“…1,27 MC4R harbours several susceptibility loci for obesity. 6,28,29 Known functional SNPs in MC4R are all rare, have been found mostly in obesity studies and mostly associate with elevated BMI. The missense variant V103I (rs2229616), however, is relatively frequent and well-studied in population-based samples.…”
Section: Introductionmentioning
confidence: 99%